INVESTMENT TOOLS FOR DOMESTIC INNOVATIVE BUSINESS SUPPORT AT REGIONAL AND LOCAL LEVELS - BILYK, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the study, the focus of attention is drawn to local economic development and the use of two fairly important and systematic factors for such purposes, such as innovative entrepreneurship and investments in the development of local innovative business. From such positions, the purpose of the study is to substantiate effective investment tools for supporting and stimulating the development of domestic innovative business at the regional and local levels. Interrelationships are proved and the algorithm of tasks (which should turn into events) is shown, from stimulating the development of entrepreneurship, improving its investment support and activating innovative activities to strengthening the investment and innovation component of Ukraine's economic security. The goal of such a policy has been determined - the formation of sufficient financial and investment resources for the purpose of increasing the volume and pace of innovative activity of innovative business entities. It was established that the leading investment instruments (and measures within their limits) that should be implemented for the following purposes should be defined: investment-infrastructural (with measures of public-private partnership in the field of implementation of innovative technological projects, financial leasing and outsourcing to attract technical technological base for R&D, creation of industrial investment and innovation parks, development of infrastructure for financing innovation activities, creation of investment and innovation clusters, other associations, activities of local economic development agencies); credit (using local bond loans for research and development, guarantees for innovation investments, bank lending for innovative projects); grant (with local grant innovation programs, involvement of international technical assistance); creation of specialized investment funds (with crowdfunding measures and the use of revolving funds); budgetary investment support (local target programs for supporting innovative activities, tax incentives for innovations, inter-municipal cooperation in the innovative and technological sphere, budgets for participation in innovative socially significant projects); entrepreneurial (with measures for the development of local innovative entrepreneurship, attracting investments of labor migrants, investment cooperation of small businesses with large enterprises in the innovation sphere).
Keywords: local economic development; entrepreneurship; entrepreneurial sector; innovative business; development; innovative activity; investment instruments